Why do people stay? Insider advantages and immobility - Peter A. Fischer; Einar Holm; Gunnar Malmberg; Thomas Straubhaar (Hamburg Institute of International Economics (HWWA), 2000)
The low mobility of people in Europe is considered a problem for adjustment to asymmetric shocks and regional convergence in the European Monetary Union. We suggest a complement to the traditional migration theories, the insider advantages approach to explain why most Europeans prefer to stay. Staying immobile they have accumulated work- and leisure-oriented insider advantages that are location-specific and would be lost in the case of emigration. Therefore, the longer people have stayed -and the more insider advantages they have accumulated-, the less likely they are to move. Using a new micro dataset covering all people resident in Sweden in 1994 and their mobility experience since 1985, we find a strong positive duration dependence of the probability to stay. Traditional micro-economic characteristics prove helpful in explaining immobility, while regional macro-economic differences have surprisingly little impact on individual mobility decisions. A large proportion of the moves between Swedish labour markets seem to be related to specific life-course events rather than to pure labour market issues. – – Wieso ist die Mobilität der Arbeitskräfte innerhalb der Europäischen Union - aller Freizügigkeit zum Trotz - so gering? Traditionelle Theorieansätze vermögen die schwach ausgeprägte Wanderungsintensität der EU-Angehörigen nur begrenzt zu erklären. Denn eigentlich sollten die teilweise beträchtlichen Einkommens- und Beschäftigungsunterschiede zu weit mehr Migration innerhalb der EU führen. In diesem Diskussionspapier entwickeln wir eine Idee, die sehr wohl zu erklären vermag, weshalb für die meisten Menschen "stehen" die bessere Alternative als "gehen" ist. Der Insider-Ansatz macht deutlich, weshalb für die individuelle Entscheidung eine grenz- und kulturraumüberschreitende Wanderung die Ausnahme und nicht die Regel ist. Die empirische Überprüfung mit Hilfe eines neuen originären Mikro-Datensets, das die gesamte schwedische Wohnbevölkerung enthält, bestätigt die These, dass die Verweildauer einen direkten positiven Einfluss auf die Verharrenswahrscheinlichkeit ausübt. Wer lange an einem Ort lebt, wird immer wahrscheinlicher an diesem Ort bleiben!
Keywords: R23; J60; F22; 330; Regionale Arbeitsmobilität; Binnenwanderung; Internationale Wanderung; Migrationstheorie; Wohnstandort; Schätzung; Theorie; Schweden